'The Ethiopian famine' revisited: Band Aid and the antipolitics of celebrity humanitarian action. Issue 1 (16th October 2012) - Müller, Tanja R.
<x xml:space="preserve">Abstract</x> In many ways the Ethiopian famine of 1983–85 has served as a watershed with respect to humanitarian action. One of its lasting legacies has been the emergence of Band Aid and the subsequent increase in celebrity humanitarianism. A revisiting of the events of 1983–85 occurred in 2010 during a dispute in which it was alleged that a portion of the donations of Band Aid were spent on arms purchases. This paper takes this controversy as its starting point. It goes on to use the theoretical reflections of Giorgio Agamben to consider the dynamics that unfolded during the Ethiopian famine of 1983–85 and to analyse the underlying conceptualisation behind the emergence of Band Aid‐type celebrity humanitarianism. The paper concludes with some wider thoughts on how the in essence antipolitical agenda of celebrity humanitarian action is transported into the everyday understanding of 'African disaster', resulting ultimately in the perpetuation of hegemonic control by the global North.